Evaluation of the Auditory Effects in Controlled and Uncontrolled Type 2 Diabetes Mellitus Using Otoacoustic Emissions (Annals of Medical Research, 2021)
None
Keywords: Hearing Loss; Non-Insulin Dependent Diabetes Mellitus; Metabolic Control; Otoacoustic Emission.